IN VITRO ANTIMICROBIAL AND ANTIOXIDANT ACTIVITIES OF THE ESSENTIAL OILS OF OCIMUM GRATISSIMUM, O. SANCTUM - Vivek G. Pete,; Chetan V. Ghulaxe,; Mahesh S. Gadge,; Ashish R. Chaudhari,; Mukesh Kumar Meena,; Reshma MG,; Nilesh Ramesh Bonde,; G. Jaya Vasavi, (The Bioscan, 2026)
The growing crisis of antimicrobial resistance (AMR) and consumer interest in natural essential oils has increased the interest in research on plant-based essential oils. The medicinal plants Ocimum gratissimum (clove basil) and Ocimum sanctum (holy basil/Tulsi) are traditionally venerated but the chemical profile and bioactivity of their essential oils in the biodiversity-rich Western Ghats of North Karnataka have not been studied. To describe volatile chemical composition and measure in vitro antimicrobial and antioxidant activity of essential oils of O. gratissimum and O. sanctum growing in this understudied area and their key isolated compounds. The essential oils were obtained through the process of steam distillation of fresh flowering aerial parts. GC and GC-MS were used to characterize the chemical. Column chromatography was used to isolate the major constituents which were eugenol of O. gratissimum and methyl eugenol of O. sanctum, and confirmed by NMR. The tube-dilution method was used to determine minimum inhibitory concentrations (MICs) of 18 microbial strains (Gram-positive, Gram-negative, and fungi) in antimicrobial activity. The antioxidant activity was assessed by the DPPH and ABTS radical scavenging tests. O. gratissimum produced 1.24% (w/w) pale yellow oil that was dominated by eugenol (68.4) and O. sanctum produced 0.98% (w/w) light brown oil that was dominated by methyl eugenol (57.6). The O. gratissimum oil, which is rich in eugenol, exhibited high antimicrobial activity, especially against Gram-positive bacteria (MIC: 0.15-0.62 mg/ml), with purified eugenol being more active (MIC: 0.08-0.31 mg/ml against S. aureus and S. epidermidis). Methyl eugenol was much less efficient (MIC: 0.622.50 mg/ml). O. gratissimum oil and eugenol were moderate against fungi (P. chrysogenum MIC: 0.31 mg/ml), whereas methyl eugenol was not very active (MIC >5.0 mg/ml). Eugenol had a high radical scavenging capacity (DPPH IC 50: 0.18 mg/ml; ABTS IC 50: 0.12mg/ml) in the antioxidant assays and was similar to Trolox. Methyl eugenol was more than 25 times less active (DPPH IC 0: 4.80 mg/ml) and O. sanctum oil had low antioxidant capacity (DPPH IC 0: 5.20 mg/ml). Free phenolic hydroxyl group of eugenol is of significant importance to both the strong antimicrobial and antioxidant properties but the methylation of eugenol to methyl eugenol drastically decreases bioactivity. The chemotype that has high eugenol content in O. gratissimum in the Western Ghats of North Karnataka is a good source of bioactive compounds. This omnipresent oil and its principal component eugenol should be further investigated as a prospective drug, preservative in natural foodstuffs, and complementary medicine in the battle against AMR and oxidative stress disease.